Improving the Quality of Financial Records Towards the Effectiveness of MSME Business Management Yera Reflection Bandar Lampung - Lase, Bernard Putra Fajar Jaya; Ardansyah, Ardansyah (LPPPIPublishing, 2024)
In preparing financial reporting, entrepreneurs can use financial accounting standards (SAK). Financial Accounting Standards (SAK) is a standard that regulates the process of preparing and presenting financial statements in order to create uniformity that can be understood by various stakeholders. However, not many MSME entrepreneurs apply financial accounting standards to manage their business financial reports. Improving the quality of financial reporting can support the effectiveness of business management. This study aims to look at the quality of financial reporting of Yera Reflexology and its impact on the effectiveness of business management. The Method have used qualitative descriptive. In this study using three techniques for data collection, namely data reduction, data presentation, conclusion drawing. From the results of research conducted at Yera Reflexology, it shows that the financial reporting carried out is still very simple and not in accordance with financial accounting standards. Yera reflection's financial report are still classified as very simple because business owners do not have knowledge of financial accounting standards for MSME so that business owners cannot present complete financial information.